Integrating Palolai Local Wisdom Through Culturally Responsive Teaching in Baubau Elementary Schools - Minsih Minsih; Ratnasari Diah Utami; Maryam Nurlaila; Uslan Uslan; Siti Marpuah (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractThis study examines the integration of Palolai local wisdom through the Culturally Responsive Teaching (CRT) approach at elementary schools in Baubau City, Southeast Sulawesi. Using a qualitative ethnographic design, data were collected through observation, interviews, documentation studies, and focus group discussions. Triangulation of sources and methods guaranteed data validity, while data analysis utilized reduction, display, and conclusion techniques. The findings reveal three key outcomes: (1) teachers effectively developed strategies to integrate Palolai wisdom into the independent curriculum via CRT; (2) CRT implementation significantly enhanced student participation in IPAS subjects; and (3) the approach successfully strengthened students' cultural identity within the Baubau community. In conclusion, the CRT approach serves as an effective pedagogical bridge, connecting formal education with local cultural values. The integration of Palolai wisdom not only enriches the curriculum but also fosters both active student engagement and robust cultural identity preservation. This study emphasizes the need to use culturally grounded approaches in education to maintain local heritage while achieving contemporary learning objectives.Keywords: culturally responsive teaching, palolai local wisdom, teacher's role. AbstrakStudi ini mengkaji integrasi kearifan lokal Palolai melalui pendekatan Pengajaran Responsif Budaya (PKB) di sekolah dasar di Kota Baubau, Sulawesi Tenggara. Dengan menggunakan desain etnografi kualitatif, data dikumpulkan melalui observasi, wawancara, studi dokumentasi, dan diskusi kelompok terfokus. Triangulasi sumber dan metode menjamin validitas data, sementara analisis data menggunakan teknik reduksi, penyajian, dan kesimpulan. Temuan ini mengungkapkan tiga hasil utama: (1) Guru secara efektif mengembangkan strategi untuk mengintegrasikan kearifan Palolai ke dalam kurikulum independen melalui PKB; (2) Implementasi PKB secara signifikan meningkatkan partisipasi siswa dalam mata pelajaran IPAS; dan (3) pendekatan ini berhasil memperkuat identitas budaya siswa dalam komunitas Baubau. Kesimpulannya, pendekatan PKB berfungsi sebagai jembatan pedagogis yang efektif, menghubungkan pendidikan formal dengan nilai-nilai budaya lokal. Integrasi kearifan Palolai tidak hanya memperkaya kurikulum tetapi juga mendorong keterlibatan aktif siswa dan pelestarian identitas budaya yang kuat. Studi ini menekankan perlunya menggunakan pendekatan yang berlandaskan budaya dalam pendidikan untuk melestarikan warisan lokal sekaligus mencapai tujuan pembelajaran kontemporer.Kata kunci: pengajaran responsif budaya, kearifan lokal palolai, peran guru.